2001
DOI: 10.1007/s11664-001-0129-5
|View full text |Cite
|
Sign up to set email alerts
|

Alloying effects in near-eutectic Sn-Ag-Cu solder alloys for improved microstructural stability

Abstract: This study included a comparison of the baseline Sn-3.5Ag eutectic to one neareutectic ternary alloy, Sn-3.6Ag-1.0Cu and two quaternary alloys, Sn-3.6Ag-1.0Cu-0.15Co and Sn-3.6Ag-1.0Cu-0.45Co, to increase understanding of the beneficial effects of Co on Sn-Ag-Cu solder joints cooled at 1-3∞C/sec, typical of reflow practice. The results indicated that joint microstructure refinement is due to Co-enhanced nucleation of the Cu 6 Sn 5 phase in the solder matrix, as suggested by Auger elemental mapping and calorime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(149 citation statements)
references
References 10 publications
4
134
0
1
Order By: Relevance
“…One approach to controlling melt undercooling is microalloying SAC with a dilute addition of certain fourth elements, and these SAC-X solders (X is the addition element) have been studied for more than a decade [15][16][17][18][19]. It has been found that Co additions are particularly effective at suppressing the nucleation undercooling of βSn [20][21][22][23][24][25][26][27][28][29].…”
Section: The Paper Published In Journal Of Alloys and Compounds In 2016mentioning
confidence: 99%
“…One approach to controlling melt undercooling is microalloying SAC with a dilute addition of certain fourth elements, and these SAC-X solders (X is the addition element) have been studied for more than a decade [15][16][17][18][19]. It has been found that Co additions are particularly effective at suppressing the nucleation undercooling of βSn [20][21][22][23][24][25][26][27][28][29].…”
Section: The Paper Published In Journal Of Alloys and Compounds In 2016mentioning
confidence: 99%
“…This form is dispersed thoroughly in the bulk alloy. 5,8 Due to the small size of these oxides, they have not been determined exactly.…”
Section: Particle Sizementioning
confidence: 99%
“…[5][6][7][8][9][10] They are widely used in Sn-Zn, Sn-Ag, and Ag-Cu alloys. [6][7][8] Lanthanum (La) is considered as a good additive due to its lower cost, wide availability, and low melting point 4 as compared with other RE elements.…”
Section: Introductionmentioning
confidence: 99%
“…Among several candidate Pb-free alloy systems, the nearternary-eutectic Sn-Ag-Cu alloys with a melting temperature around 217 C are becoming a leading candidate, [1][2][3] especially for SMT card assembly including BGA solder joints. The near-eutectic, commercially available alloys include Sn-4.0Ag-0.5Cu, Sn-3.9Ag-0.6Cu, Sn-3.8Ag-0.7Cu, and Sn-3.0Ag-0.5Cu (in mass%).…”
Section: Near Ternary Eutectic Sn-ag-cu Alloysmentioning
confidence: 99%